(untitled) (Bangladesh Journal of Plant Taxonomy, 2011)
Not available Keywords: Castanopsis; China; Fagaceae; Hainan; Nomenclature; Validation. DOI: 10.3329/bjpt.v18i1.7843 Bangladesh J. Plant Taxon. 18(1): 77-79, 2011 (June)